Experimental Evaluations on Braking Responses of Magnetorheological Brake - Zainordin, Ahmad Zaifazlin; ABDULLAH, Mohd Azman; Hudha, Khisbullah (2013)
This paper presents experimental evaluations on braking responses of Magnetorheological Brake (MR Brake) at various current and load. The MR brake consists of a rotating disk that immersed with Magnetorheological Fluid (MR Fluid) where the fluid behavior is changing under influence of magnetic fields. The experiments are performed using MR brake test rig to obtain three output responses namely the angular velocity response, torque response and load displacement response. The MR brake generates maximum torque at high current and causes fast decrement of shaft angular velocity. The effectiveness MR brake torque happens at minimum load with low stopping time.